Update in Antiepidermal Growth Factor Receptor Therapy in the Management of Metastatic Colorectal Cancer. (8th April 2009) - Loong, Herbert H.; Ma, Brigette B.; Chan, Anthony T. C.
Abstract : The approval of anti-epidermal growth factor receptor (EGFR) monoclonal antibodies in the treatment of metastatic colorectal cancer (CRC) has expanded the armamentarium against this disease. This paper will review the historical progress and recent clinical developments of anti-EGFR therapies in the treatment of metastatic CRC. Novel strategies of targeting the EGFR pathway to improve efficacy as well as ongoing research in identifying specific molecular predictors of response will be discussed.